Declining histone acetyltransferase GCN5 represses BMSC‐mediated angiogenesis during osteoporosis. Issue 10 (19th September 2017) - Jing, Huan; Liao, Li; Su, Xiaoxia; Shuai, Yi; Zhang, Xinjing; Deng, Zhihong; Jin, Yan
ABSTRACT: Angiogenesis is disrupted in age‐related and postmenopausal osteoporosis. However, the mechanisms of the disorder remain elusive. We confirmed in this study that, in accordance with the decrease of H‐type vessels, the proangiogenic potential of bone marrow‐derived mesenchymal stem cells (BMSCs) declined during osteoporosis. Screening of the histone acetyltransferase family revealed that GCN5 decreased in BMSCs derived from osteoporotic femur. Further analysis identified that GCN5 plays important roles in regulating the proangiogenic potential of BMSCs. GCN5 promoted BMSC‐mediated angiogenesis by enhancing H3K9ac levels on the promoter of Vegf . The decrease of GCN5 in osteoporotic BMSCs led to the decline of proangiogenic capacity. Accordingly, overexpression of GCN5 enhanced the proangiogenic potency of osteoporotic BMSCs. Furthermore, recovering GCN5 expression in vivo by lentiviral expression vector significantly attenuated the loss of angiogenesis in ovariectomized mouse femurs. Our study results revealed an epigenetic mechanism controlling BMSC‐mediated angiogenesis and provided a novel therapeutic target for osteoporosis treatment.—Jing, H., Liao, L., Su, X., Shuai, Y. Zhang, X., Deng, Z., Jin, Y. Declining histone acetyltransferase GCN5 represses BMSC‐mediated angiogenesis during osteoporosis. FASEB J. 31, 4422–4433 (2017). www.fasebj.org